Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1987
DOI: 10.1088/0264-9381/4/5/010
|View full text |Cite
|
Sign up to set email alerts
|

General future asymptotically flat spacetimes

Abstract: The standard notions of asymptotically flat spacetimes have been challenged by the examples found by Isaacson, Welling and Winicour (1984), which show logarithmic asymptotic behaviour. Here, a geometrical definition of general future asymptotically flat (GeFAF) spacetimes is introduced, and its implications are systematically studied throughout the paper. Conformal techniques are used, but no reference to field equations is made. In particular logarithmic behaviour is studied. For the general GeFAF case it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(66 citation statements)
references
References 12 publications
0
66
0
Order By: Relevance
“…(12). We also define a spinor on M by ψ ABCD ω −1 Ψ ABCD , which we can extend continuously to I + .…”
Section: At Every Point Of Imentioning
confidence: 99%
See 4 more Smart Citations
“…(12). We also define a spinor on M by ψ ABCD ω −1 Ψ ABCD , which we can extend continuously to I + .…”
Section: At Every Point Of Imentioning
confidence: 99%
“…These coordinates can be extended into a neighborhood of I + by taking ω as an additional coordinate along futuredirected null geodesics, where (u, θ, φ) labels the geodesics. Moreschi [12] showed that, up to irrelevant gauge freedom, the ω function is related to the luminosity distance r L by…”
Section: At Every Point Of Imentioning
confidence: 99%
See 3 more Smart Citations